2016
DOI: 10.1186/s40795-016-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Leucine disposal rate for assessment of amino acid metabolism in maintenance hemodialysis patients

Abstract: Background Protein energy wasting (PEW) is common in patients undergoing maintenance hemodialysis (MHD) and closely associated with poor outcomes. Insulin resistance and associated alterations in amino acid metabolism are potential pathways leading to PEW. We hypothesized that the measurement of leucine disposal during a hyperinsulinemic- euglycemic-euaminoacidemic clamp (HEAC) procedure would accurately measure the sensitivity to insulin for its actions on concomitant carbohydrate and protein metabolism in MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…LDR used in this study is based on the same principal but directly assesses insulin sensitivity in terms of amino acid metabolism. We have reported that there is excellent correlation between LDR and whole body protein metabolism estimated by stable isotope studies in both healthy individuals and patients on MHD . The data reported herein suggest that the mechanisms by which insulin sensitivity is altered due to muscle tissue Na + accumulation share a common signaling pathway for both carbohydrate and amino acid metabolism, which occurs predominantly when skeletal muscle is excessively Na + overloaded.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…LDR used in this study is based on the same principal but directly assesses insulin sensitivity in terms of amino acid metabolism. We have reported that there is excellent correlation between LDR and whole body protein metabolism estimated by stable isotope studies in both healthy individuals and patients on MHD . The data reported herein suggest that the mechanisms by which insulin sensitivity is altered due to muscle tissue Na + accumulation share a common signaling pathway for both carbohydrate and amino acid metabolism, which occurs predominantly when skeletal muscle is excessively Na + overloaded.…”
Section: Discussionsupporting
confidence: 53%
“…While earlier studies have reported significant differences in GDR between MHD patients compared with healthy controls, recent data by our group and others suggest that resistance to glycogenic effects of insulin is determined by mechanisms besides the uremic milieu in CKD patients, including ones on maintenance dialysis . On the other hand, we have shown that resistance to anabolic actions of insulin is a direct consequence of underlying CKD, unlike insulin's glycogenic actions . These observations are based on methodology that is considered to be the gold standard for assessment of insulin sensitivity.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations